2012
DOI: 10.1364/ome.2.001353
|View full text |Cite
|
Sign up to set email alerts
|

Bistable state in polymer stabilized blue phase liquid crystal

Abstract: The bistable phenomenon is found in polymer stabilized blue phase liquid crystal. Two stable phases, blue phase and chiral nematic state, are obtained and we succeeded in the switch between these two states through different operation procedures. The mechanism of the bistable phenomenon is discussed, according to which we consider the bistability may widely exist in various polymer stabilized blue phase liquid crystal systems. This work provides some useful insights into the application of polymer stabilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Wang et al reported the bistable states of BP I and BP II that found in BP LCs system, and their phase transition behaviors were also studied [27] . The PSBP bistability was also found [28] . Unlike conventional PSBP, which went from PSBP directly to field-induced vertical alignment (VA) when driven by saturated electric field, an intermediate chiral nematic phase was observed between the above two states when the applied field was increased slowly to the saturation.…”
mentioning
confidence: 85%
“…Wang et al reported the bistable states of BP I and BP II that found in BP LCs system, and their phase transition behaviors were also studied [27] . The PSBP bistability was also found [28] . Unlike conventional PSBP, which went from PSBP directly to field-induced vertical alignment (VA) when driven by saturated electric field, an intermediate chiral nematic phase was observed between the above two states when the applied field was increased slowly to the saturation.…”
mentioning
confidence: 85%
“…[11][12][13][14][15][16][17][18][19][20][21][22] Among them, a polymer stabilized blue phase liquid crystal (PS-BPLC) is the most efficient method to stabilize BPs as polymer networks could concentrate in the isotropic defect core and localize the disclination core of the BP structure. 11,12 Besides polymer networks, molecular designs have been widely adopted as a method to stabilize BPs such as hydrogen bond molecules, 13 bimesogenic molecules, T-shaped molecules 15,16 and bent-core molecules. [17][18][19][20][21] Additionally, other methods like nanoparticles 22 have also been used to widen the temperature range of BPs.…”
Section: Introductionmentioning
confidence: 99%
“…Bistable liquid crystal display (BLCD) has attracted intensive attentions thanks to the feature of power required only in updating images while electrical field unneeded in maintaining off/on states [1][2][3][4][5][6][7]. Therefore it is quite suitable for displays that would not be frequently updated, such as electronic signage cards, e-books, and even large electronic billboards.…”
Section: Introductionmentioning
confidence: 99%